Chorioamnionitis at birth does not increase the risk of neurodevelopmental disability in premature infants with bronchopulmonary dysplasia. (November 2016) - Bashir, Rani A.; Bhandari, Vineet; Vayalthrikkovil, Sakeer; Rabi, Yacov; Soraisham, Amuchou; Tang, Selphee; Al Awad, Essa; Lodha, Abhay
Abstract: Aim: To compare preterm infants with no bronchopulmonary dysplasia (BPD), BPD with chorioamnionitis (BPDC) and BPD with no chorioamnionitis (BPDNC) for the association with neurodevelopmental disability (NDD) at three years corrected age. Methods: Demographic and outcome data of infants with birthweight (BW) ≤1250 g born during two epochs (1995–2000 and 2002–2007 with an interim washout period of one year) were compared on the basis of whether they had BPD, chorioamnionitis or both. Any NDD was considered present if there was either mild–severe cerebral palsy (CP), cognitive delay, visual or hearing impairment. Logistic regression modelling was performed. Results: Infants (n = 1009) were included into three groups – no BPD (n = 442), BPDNC (n = 437) and BPDC (n = 130). The adjusted odds ratio (aOR) of any NDD at three years in infants with BPDC versus BPDNC was 1.37; 95% CI 0.85–2.20, and for CP the aOR was 1.66; 95% CI 0.76–3.62. Infants in the BPDC group were of lower BW, gestational age and had longer length of hospital stay, duration of mechanical ventilation, more blood transfusions and sepsis compared to BPDNC and no BPD groups (all p < 0.001). Conclusion: Chorioamnionitis was not associated with any increase in the odds of NDD in infants with BPD at three years corrected age.